2017
DOI: 10.1038/nchem.2736
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-modulated conformational switching in a fully synthetic membrane-bound receptor

Abstract: . Ligandmodulated conformational switching in a fully synthetic membrane-bound receptor. Nature Chemistry, 9(5), [420][421][422][423][424][425] University of Bristol -Explore Bristol Research General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. AbstractSignal transduction through G protein-coupled receptors (GPCRs) involves binding to signalling molecules at the cell surface, which leads to global changes in mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
94
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(102 citation statements)
references
References 42 publications
1
94
0
Order By: Relevance
“…Incorporation of a urea-based anion recognition site into an amide foldamer allows the foldamer to respond to an environmental signal -a hydrogen-bonded interaction with a chiral anion -by changing its global conformational preference. This simple hydrogen-bonded mechanism of interaction complements the design of related binding sites based on boron, 35 copper, 37 or basic nitrogen 32 centres. Non-covalent interaction mediated by hydrogen bonding leads to solvent-dependent asymmetric induction of screw sense preference to differing extents, according to the pairing of various binding sites with various chiral phosphates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Incorporation of a urea-based anion recognition site into an amide foldamer allows the foldamer to respond to an environmental signal -a hydrogen-bonded interaction with a chiral anion -by changing its global conformational preference. This simple hydrogen-bonded mechanism of interaction complements the design of related binding sites based on boron, 35 copper, 37 or basic nitrogen 32 centres. Non-covalent interaction mediated by hydrogen bonding leads to solvent-dependent asymmetric induction of screw sense preference to differing extents, according to the pairing of various binding sites with various chiral phosphates.…”
Section: Discussionmentioning
confidence: 99%
“…32 Other examples similarly made use of specific functionality at a designed binding site (for example incorporating a boron, 35 zinc, 23 or copper 37 based 'cofactor') to enforce selective interactions with the foldamer chain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies reveal that molecular chirality directs whole-cell chirality XXXI [8]. At the cellular level, signal transduction involves the wave of chiral transformations in the protein-phospholipid interactions [204][205][206].…”
Section: From Molecular To Cellular Levelmentioning
confidence: 99%
“…[3][4][5][6][7][8][9] However, mimicking signal transduction and amplification processes that occur without physical transfer of matter has proved a considerable challenge for synthetic systems. [10][11][12][13][14][15] Recently, we have shown that a new abiotic mechanism -membrane translocation -can be used for signal transduction across lipid bilayers in artificial systems ( Figure 1a). The reversible movement of a synthetic transducer molecule across a bilayer can be controlled by chemical input signals on the outside of the vesicle.…”
Section: Introductionmentioning
confidence: 99%